2014
DOI: 10.1097/sle.0b013e31828fa45e
|View full text |Cite
|
Sign up to set email alerts
|

Can Percutaneous Cholecystostomy be a Definitive Management for Acute Cholecystitis in High-risk Patients?

Abstract: PC is a safe and efficient treatment option for patients with AC who are less eligible for surgery. After patients recover from PC, further treatment such as cholecystectomy may not be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
25
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
1
25
0
1
Order By: Relevance
“…On the basis of our long-term experience [2][3][4][5], we would like to highlight certain issues of the possibility of percutaneous cholecystostomy (PC) as the treatment modality for AC in elderly patients. In these high-risk patients, PC as a less aggressive method compared with surgery, performed without general anesthesia, has been shown to be a lifesaving, minimally invasive, alternative management.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…On the basis of our long-term experience [2][3][4][5], we would like to highlight certain issues of the possibility of percutaneous cholecystostomy (PC) as the treatment modality for AC in elderly patients. In these high-risk patients, PC as a less aggressive method compared with surgery, performed without general anesthesia, has been shown to be a lifesaving, minimally invasive, alternative management.…”
mentioning
confidence: 99%
“…Since then, numerous reports have shown the efficacy of PC for the treatment of AC in high-risk and elderly patients [2][3][4][5][6][7][8][9]. However, to date, it remains controversial whether this method should be used as a temporary measure to postpone the definitive cholecystectomy to an elective setting or whether this procedure itself may be the definitive treatment [2,[4][5][6][7][8][9].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…11 For such cases, PC drainage may be used either as a bridge towards a delayed LC or in higher-risk patients (ASA Grades III and IV) as definitive therapy. 12,13 The role in selected patients of an entirely conservative approach demands further prospective study. In this respect, Hatzidakis et al 14 showed no difference in outcome when comparing PC plus antibiotic therapy with conservative treatment alone with Akyurek and colleagues 15 suggesting that PC followed by early LC has a generally more favourable outcome than conservative treatment and a delayed LC approach.…”
Section: Introductionmentioning
confidence: 99%